The life and wars of Gideon J. Pillow - Hughes, Nathaniel Cheairs, Jr., 1930-2012 (University of Tennessee Press, 2011)
One of nineteenth-century America's most controversial military figures, Gideon Johnson Pillow gained notoriety early in the Civil War for turning an apparent Confederate victory at Fort Donelson into an ignominious defeat. Dismissed by contemporaries and historians alike as a political general with dangerous aspirations, his famous failures have overshadowed the tremendous energy, rare talent, and great organizational skills that also marked his career. In this exhaustive biography, Nathaniel Cheairs Hughes Jr. and Roy P. Stonesifer Jr. look beyond conventional historical interp.